Evaluacion de cepas del hongo entomopatogeno beauveria baáiana (Bals.) Vuill. para el combate de atta insularis (Guerin) - Trujillo, Z.=700 1 Perez, R.; Lopez, M.; Zamora, C.N.; Ocano, C.
(Es, En)
Ilus., 18 ref.
Keywords: ATTA INSULARIS; BEAUVERIA BAáIANA; HONGOS ENTOMOPATOGENOS; CONTROL DE PLAGAS; CUBA